Implementasi Strategi Pembelajaran Ekspositori dalam Pendidikan Agama Islam - Azil Hanifa Azzahra; Gusmaneli Gusmaneli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The expository learning strategy in Islamic Religious Education (PAI) remains relevant as a classical Islamic scholarly heritage but requires creative transformation to address digital-age challenges. This article examines the implementation of expository strategies through literature study, analyzing philosophical foundations, effectiveness, contemporary challenges, and innovation models. The research reveals that expository strategies are effective for normative PAI materials but face complex challenges including shifting cognitive patterns of digital natives, decentralization of knowledge authority, and technological disparities. Various innovative models (interactive, contextual, multimedia, reflective) offer solutions by integrating traditional expository strengths with modern approaches. The study concludes that successful implementation requires paradigmatic reconstruction through